Prospects for the use of geotubes in the mining industry - Kislyakov, Victor; Zubov, Pavel A.; Kokorev, Aleksandr (Journal of Degraded and Mining Lands Management, 2025)
The use of geosynthetic containers (geotubes) is a promising technology for the elimination of environmental pollution from industrial and subsurface use waste, based on the storage and dewatering of liquefied waste inside geosynthetic shells. The problem of environmental pollution from the mining industry is relevant since this industry is one of the leading areas of the world economy. Geotubes have found their application to solve some of the challenges facing the industry. However, in most cases, geotubes are not integrated into technological processes and do not use all the possibilities of their application. The data, effective methods, and technologies, examples of applications in various areas of the mining industry. he main advantages and disadvantages of technologies are presented. Examples of the use of geotubes in mining, including the development of placer deposits, the construction of structures, the operation of sludge storages, dumps, are considered.